Research into practice : evidence-informed, best practice visualisation for a deeper understanding of science : final report. - Tasker, Roy (Australia. Dept of Education and Training (DET), 2019)
For most people, learning science involves imagining invisible phenomena—such as molecular-level structures and processes, force fields and energy changes—to explain observable experiences—like stickiness, magnetic repulsion and hot objects—in order to create new insights. Mental modelling of these imperceptible phenomena through visualisation is the key to making meaning from the symbolism and mathematics in science that too often alienate novice students. Only when you have useful visual mental models of these invisible phenomena can you see the power of mathematics to generalise from the specific, and meaningfully communicate about these phenomena using scientific shorthand (symbols, formulas, equations), terminology, and language. Visualisation in science is usually complex and dynamic, so it is cognitively demanding. Consequently, best-practice use of visualisation in science teaching should be informed by the latest cognitive science research on factors determining how the brain perceives, processes, stores and retrieves audiovisual information, and ways to ameliorate this load. We also need to encourage learners to communicate their visual models orally, in writing, and through storyboards (labelled drawings), to probe for misconceptions. The unique aspect of this fellowship was to stimulate strategic and embedded use of visualisation in science teaching by applying findings in learning research in three distinct disciplines—science education, multimedia education and cognitive science—whose practitioners rarely read one another's published research or attend one another's conferences. [Executive summary, ed]